Triage of Means: Options for Conserving Tiger Corridors beyond Designated Protected Lands in India - Mondal, Indranil; Habib, Bilal; Talukdar, Gautam; Nigam, Parag (Frontiers in Ecology and Evolution, 2016)
The latest tiger census conducted in India during the year 2014 shows that it harbours 57% of the global tiger population in 7% of their historic global range. At the same time, India has 1.25 billion people growing at a rate of 1.7% per year. Protected tiger habitats in India are geographically isolated and collectively holds this tiger population under tremendous anthropogenic pressure. These protected lands are in itself not enough to sustain the growing tiger population, intensifying human-tiger conflict as dispersing individuals enter human occupied areas. These factors – isolation and inadequate size of the protected lands harbouring tiger meta-populations, highlight the need to connect tiger habitats and the importance of corridors beyond protected lands. It is imperative to conserve such corridors passing through private lands to safeguard the long-term survival of the tigers in India. The goal of long-term tiger conservation in India lies in smartly integrating tiger conservation concerns in various sectors where tiger conservation is not the priority. To effectively tap into all these resources, we propose a “Triage of Means” strategy. Here we do not prioritize species, populations or sites due to the non-availability of conservation resources. Instead, we aim to prioritize from available resources (means to achieve conservation) from other sectors where tiger conservation is not the focus. We outline how to prioritise resources available from various sectors into conservation by prioritizing issues hampering tiger conservation beyond protected habitats.